On Generalized Digital Topology and Root Images of Median Filters - Osama Tantawy; Sobhy El Shiekh; Mohamed Yakout; Sawsan El Sayed (Journal of New Theory)
In this paper, we extend the concepts of semi-open sets and λ-open sets in the digital topology. In addition, we introduce the concepts of regular semi-open and regular λ-open sets. A relationship between digital topology and image processing is established.